A high fat diet increases mitochondrial fatty acid oxidation and uncoupling to decrease efficiency in rat heart. - M.A, Cole; A.J, Murray; L.E, Cochlin; L.C, Heather; S., McAleese; N.S, Knight; E., Sutton; Abd. Jamil, Amira Hajirah; N., Parassol; K., Clarke (Springer Medizin, 2011)
Elevated levels of cardiac mitochondrial uncoupling protein 3 (UCP3) and decreased cardiac efficiency (hydraulic power/oxygen consumption) with abnormal cardiac function occur in obese, diabetic mice. To determine whether cardiac mitochondrial uncoupling occurs in non-genetic obesity, we fed rats a high fat diet (55% kcal from fat) or standard laboratory chow (7% kcal from fat) for 3 weeks, after which we measured cardiac function in vivo using cine MRI, efficiency in isolated working hearts and respiration rates and ADP/O ratios in isolated interfibrillar mitochondria; also, measured were medium chain acyl-CoA dehydrogenase (MCAD) and citrate synthase activities plus uncoupling protein 3 (UCP3), mitochondrial thioesterase 1 (MTE-1), adenine nucleotide translocase (ANT) and ATP synthase protein levels. We found that in vivo cardiac function was the same for all rats, yet oxygen consumption was 19% higher in high fatfed rat hearts, therefore, efficiency was 21% lower than in controls. We found that mitochondrial fatty acid oxidation rates were 25% higher, and MCAD activity was 23% higher, in hearts from rats fed the high fat diet when compared with controls. Mitochondria from high fat-fed rat hearts had lower ADP/O ratios than controls, indicating increased respiratory uncoupling, which was ameliorated by GDP, a UCP3 inhibitor. Mitochondrial UCP3 and MTE- 1 levels were both increased by 20% in high fat-fed rat hearts when compared with controls, with no significant change in ATP synthase or ANT levels, or citrate synthase activity. We conclude that increased cardiac oxygen utilisation, and thereby decreased cardiac efficiency, occurs in non-genetic obesity, which is associated with increased mitochondrial uncoupling due to elevated UCP3 and MTE-1 levels. Keywords Cardiac efficiency Oxygen consumption Free fatty acids Uncoupling High fat diet Mitochondria